Effect of Effective Microorganisms (EM1®) on Microflora Population and Carcass Yield of Quails - Ahmad Syazni, Kamarudin; Noor Afiza, Badaluddin; Norshida, Ismail; Zarizal, Suhaili (2018)
A total of 240 day-old Japanese quails were used to investigate the effect of EM1® on the microflora population and carcass quality of the quails in day 42 through drinking water. They were assigned randomly into four groups with 60 quails per treatments. The four treatments groups were given drinking water (DW) supplemented with EM1® (EM) with different rations which were: i) Drinking water (control group), ii) 1L EM + 250mL DW, iii) 1L EM + 500 mL DW and, iv) 1L EM + 750 mL DW. The result shows the population of Escherichia coli in the jejunum and faeces of the quails decrease significantly (p<0.05). It was also significantly increase the weight of eviscerated carcass with the value 183.17g, 210.0g, 221.0g and 225.0g and thigh weight of the quails with the value 26.57%, 31.25%, 32.01% and 33.68% for Control, T1, T2 and T3, respectively. However, the additional of EM1® into the drinking water does not significantly increase the Lactobacilli population in the jejunum and faecal sample of the quails. There were also no significant differences in the body weight and breast weight of the quails. At the end of this experiment, there is no Salmonella sp. were detected. In conclusion, quails given EM1® are suggested to reduce the number of E. coli population in intestine and produce better carcass quality.